The central role of NADPH depletion in MnTE-2-PyP-induced prostate cancer cell growth inhibition - Yuxiang Zhu (Elsevier, 2021)
Radiotherapy is commonly used in prostate cancer treatment. MnTE-2-PyP is a superoxide dismutase (SOD) mimic that can protect normal tissues from radiation toxicities while simultaneously promoting radiation-induced damage to cancer tissues. Previous work from our laboratory demonstrated that MnTE-2-PyP increased cellular H2O2 levels and led to protein oxidation and DNA damage in prostate cancer cells, which partially contributes to prostate cancer growth arrest. However, the central mechanisms by which MnTE-2-PyP reduces prostate cancer growth remain unclear. In this study, we identified that MnTE-2-PyP depleted cellular reductant levels, especially NADPH, in prostate cancer cells. Correspondingly, we observed a significant decrease in activity of glucose-6-phosphate dehydrogenase (G6PD) and 6-phosphogluconate dehydrogenase (6PGD), which are major cellular NADPH producing enzymes in the pentose phosphate pathway. A decrease of GSH/GSSG ratios were confirmed in MnTE-2-PyP-treated prostate cancer cells, which may result from the decreased glutathione reductase (GR) activity due to NADPH depletion. We also identified that MnTE-2-PyP with radiation significantly increased lipid peroxidation in prostate cancer cells and upregulated sphingomyelin synthesis, which could further consume available NADPH. Thus, MnTE-2-PyP treatment causes lower NADPH levels, resulting in more oxidative stress and membrane damage of prostate cancer cells.